Tanggung Jawab Pidana Tenaga Medis Dalam Kasus Malpraktik: Perspektif Hukum Kesehatan (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
Based on the objectives of the Republic of Indonesia, which protects every right and existence in order to provide welfare to its people, it is evident that technological advancement also has a significant impact on the healthcare world. Medical malpractice is a medical act that can be highly detrimental, as it directly affects the community by causing negligence in medical services. In this regard, legislation provides protection to the Indonesian people and safeguards their rights as recipients of healthcare services. The aim of this research is to examine the criminal responsibility of healthcare professionals in cases of malpractice. The author also employs a juridical research method, where the main issue serves as the primary data, and in order to provide strong results, legal regulations are used as secondary data to offer an assessment for addressing malpractice cases transparently. The results of this research explain that a doctor can be legally prosecuted for their negligence in providing healthcare services, both from the perspective of law and medical ethics.